Theophylline Dosing and Pharmacokinetics for Renal Protection in Neonates with Hypoxic Ischemic Encephalopathy Undergoing Therapeutic Hypothermia - Frymoyer, Adam (Pediatr Res, 2020)
BACKGROUND: Theophylline, a non-selective adenosine receptor antagonist, improves renal perfusion in the setting of hypoxia-ischemia and may offer therapeutic benefit in neonates with hypoxic ischemic encephalopathy (HIE) undergoing hypothermia. We evaluated the pharmacokinetics and dose-exposure relationships of theophylline in this population to guide dosing strategies. METHODS: A population pharmacokinetic analysis was performed in 22 neonates with HIE undergoing hypothermia who were part of a prospective study or retrospective chart review. Aminophylline (intravenous salt-form of theophylline) was given per institutional standard of care for low urine output and/or rising serum creatinine (5 mg/kg IV load then 1.8 mg/kg IV q6h). The ability of different dosing regimens to achieve target concentrations (4–10 mg/L) associated with clinical response was examined. RESULTS: Birth weight was a significant predictor of theophylline clearance and volume of distribution (p<0.05). The median half-life was 39.5 h (range 27.2 to 50.4). An aminophylline loading dose of 7 mg/kg followed by 1.6 mg/kg q12h was predicted to achieve target concentrations in 84% of simulated neonates. CONCLUSIONS: In neonates with HIE undergoing hypothermia, theophylline clearance was low with a 50% longer half-life compared to full-term normothermic neonates without HIE. Dosing strategies need to consider the unique pharmacokinetic needs of this population.